Pengaruh Current Ratio, Debt to Equity Ratio, Return on Assets, dan Total Assets Turnover Terhadap Nilai Perusahaan pada Perusahaan Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2016–2024 - Khenny El Yabes Johananta; Ingrid Panjaitan (Jurnal Minfo Polgan, 2026)
This study empirically examines the impact of Current Ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), and Total Asset Turnover (TATO) on company valuation as measured by Price to Book Value (PBV) in the Consumer Non-Cyclicals sector entities listed on the Indonesia Stock Exchange (IDX) during the 2016–2024 period. Using a purposive sampling technique, 9 sample companies were obtained, resulting in 81 observational data. The data were analyzed using multiple linear regression with the Ordinary Least Squares (OLS) approach processed using SPSS. The results of the classical assumption test indicate that the model has met the requirements for normality, multicollinearity, heteroscedasticity, and autocorrelation. Together, the four financial ratios (CR, DER, ROA, and TATO) are proven to have a significant influence on company valuation, with a calculated F value of 74.044 and a significance level below 0.001. Partially, CR shows a statistically significant positive unidirectional relationship (β = 0.787; p = 0.002), DER shows a statistically significant unidirectional relationship (β = 1.053; p = 0.018), ROA shows a statistically significant unidirectional relationship (β = 31.832; p = 0.000), and TATO shows a statistically significant unidirectional relationship (β = 1.575; p = 0.000) on firm value. Among the four variables, ROA has the largest contribution indicated by a standardized beta coefficient of 0.599. The model's explanatory power reaches 78.5% (Adjusted R² = 0.785). These findings support the signaling theory and indicate that financial ratios reflecting liquidity, leverage, profitability, and asset efficiency serve as positive signals for investors in this defensive sector.